From linguistic areas to areal linguistics - Muysken, Pieter (Studies in language companion series, 2008)
From linguistic areas to areal linguistics explores language description and typology in terms of areal background, presenting case studies in areal linguistics. Some concern well-established linguistic areas such as the Balkan, other regions such as East Nusantara (Indonesia) and the Guapore-Mamore (Amazon) regions have never before been studied in an areal perspective, and yet other areas are involved in current debates. The insight has gained ground that languages owe many of their characteristics to the languages they are in contact with over time. Yet the nature of these areal influences.